sistema interessante...
Anexos:
![](https://pt-static.z-dn.net/files/dad/5c8a5671388d4dc05f5f4415893e1ebd.png)
Soluções para a tarefa
Respondido por
1
En el primer sistema se deduce
![y_k'''-y_k=0\;,\; \text{with }k\in\{1,2,3\} y_k'''-y_k=0\;,\; \text{with }k\in\{1,2,3\}](https://tex.z-dn.net/?f=y_k%27%27%27-y_k%3D0%5C%3B%2C%5C%3B+%5Ctext%7Bwith+%7Dk%5Cin%5C%7B1%2C2%2C3%5C%7D)
![(D^3-1)y_k=0\\ \\
(D-1)(D^2+D+1)y_k=0\\
(r-1)(r^2+r+1)=0\iff r\in \left\{1,-\dfrac{1}{2}\pm \dfrac{\sqrt{3}}{2}i\right\}\\ \\
y_1=C_1e^{t}+C_2e^{-t/2}\cos \left(\dfrac{\sqrt{3}}{2}t\right)+C_3e^{-t/2}\sin \left(\dfrac{\sqrt{3}}{2}t\right)
\\ \\
(D^3-1)y_k=0\\ \\
(D-1)(D^2+D+1)y_k=0\\
(r-1)(r^2+r+1)=0\iff r\in \left\{1,-\dfrac{1}{2}\pm \dfrac{\sqrt{3}}{2}i\right\}\\ \\
y_1=C_1e^{t}+C_2e^{-t/2}\cos \left(\dfrac{\sqrt{3}}{2}t\right)+C_3e^{-t/2}\sin \left(\dfrac{\sqrt{3}}{2}t\right)
\\ \\](https://tex.z-dn.net/?f=%28D%5E3-1%29y_k%3D0%5C%5C+%5C%5C%0A%28D-1%29%28D%5E2%2BD%2B1%29y_k%3D0%5C%5C%0A%28r-1%29%28r%5E2%2Br%2B1%29%3D0%5Ciff+r%5Cin+%5Cleft%5C%7B1%2C-%5Cdfrac%7B1%7D%7B2%7D%5Cpm+%5Cdfrac%7B%5Csqrt%7B3%7D%7D%7B2%7Di%5Cright%5C%7D%5C%5C+%5C%5C%0Ay_1%3DC_1e%5E%7Bt%7D%2BC_2e%5E%7B-t%2F2%7D%5Ccos+%5Cleft%28%5Cdfrac%7B%5Csqrt%7B3%7D%7D%7B2%7Dt%5Cright%29%2BC_3e%5E%7B-t%2F2%7D%5Csin+%5Cleft%28%5Cdfrac%7B%5Csqrt%7B3%7D%7D%7B2%7Dt%5Cright%29%0A%5C%5C+%5C%5C%0A)
=================================
derivamos la primera ecuación
![y_1'' = y_2'+y_3'=2y_1+y_2+y_3\\ \\
y_1'' =2y_1+y_1'\\ \\
y_1''-y_1'-2y_1=0\\ \\
y_1'' = y_2'+y_3'=2y_1+y_2+y_3\\ \\
y_1'' =2y_1+y_1'\\ \\
y_1''-y_1'-2y_1=0\\ \\](https://tex.z-dn.net/?f=y_1%27%27+%3D+y_2%27%2By_3%27%3D2y_1%2By_2%2By_3%5C%5C+%5C%5C%0Ay_1%27%27+%3D2y_1%2By_1%27%5C%5C+%5C%5C%0Ay_1%27%27-y_1%27-2y_1%3D0%5C%5C+%5C%5C%0A)
=================================
derivamos la primera ecuación
Perguntas interessantes
Matemática,
1 ano atrás
Física,
1 ano atrás
Ed. Física,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás